2014
DOI: 10.1080/10408398.2011.630153
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Modulation of F2-Isoprostanes in Humans: A Systematic Review

Abstract: F2-isoprostanes are a biomarker of lipid peroxidation, and their measurement has emerged as a reliable approach to assess oxidative stress. However, dietary intervention studies in humans have provided contrasting results following supplementation with antioxidant-rich foods or supplements. In this paper, we have systematically reviewed the evidence about the effect of supplementation with antioxidant-rich foods and galenic antioxidants on isoprostanes levels in humans. Moreover, the association with nonenzyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 131 publications
1
17
0
Order By: Relevance
“…[113][114][115][116][117] Plasma levels as well as exhaled breath condensate were significantly higher when measured in the morning (i.e., after sleep) in patients with OSA compared to age-and weight-matched healthy obese subjects, while evening levels of 8-Isoprostanes were similar in both groups. 118 The positive correlation between morning levels of 8-isoprostane and AHI suggested an association between OSA and increased systemic and local levels of oxidative stress.…”
Section: Oxidative Stressmentioning
confidence: 82%
“…[113][114][115][116][117] Plasma levels as well as exhaled breath condensate were significantly higher when measured in the morning (i.e., after sleep) in patients with OSA compared to age-and weight-matched healthy obese subjects, while evening levels of 8-Isoprostanes were similar in both groups. 118 The positive correlation between morning levels of 8-isoprostane and AHI suggested an association between OSA and increased systemic and local levels of oxidative stress.…”
Section: Oxidative Stressmentioning
confidence: 82%
“…However, due to the extensive metabolic activity during digestion, leading to different metabolites endowed with different bioactive ingredients from parental compounds, it is still unclear which are the bioactive ingredients or metabolites responsible of the effect and their relevance in humans [98, 99, 120]. …”
Section: Discussionmentioning
confidence: 99%
“…Although NEAC assays present the advantage of integration of the individual antioxidant actions of different compounds and their additive, synergistic, or antagonistic interactions, many limitations have been pointed out previously [129, 403407] (Table 4). Different NEAC assays can give different results, both in disease states [396] and after dietary supplementation with antioxidant-rich plant foods and beverages [394, 412, 413]. In a meta-analysis, Lettieri et al [394] reported that TRAP, ORAC, and FRAP, but not TEAC, displayed an increase in plasma NEAC in both acute and chronic studies.…”
Section: Measuring the Nonenzymatic Antioxidant Capacity In Body Fmentioning
confidence: 99%
“…Despite a correspondence between the effect on F2-IsoPs (the golden standard of oxidative stress) and NEAC has been reported in 67% (14/21) of the interventions with foods and in 77% (10/13) of the interventions with galenics [413] of human studies in a systematic review, in the majority of the cases the correspondence was the lack of change for both biomarkers, whereas increases in NEAC and decreases in F2-IsoPs were observed only in 9.5% (2/21) of interventions with foods and 30.7% (4/13) of interventions with supplements [413]. Furthermore, despite gas chromatography mass spectrometry or liquid chromatography mass spectrometry techniques giving a more reliable and precise measure of F2-IsoPs, in the majority of these studies (5/6), enzyme-linked immunosorbent assay-based methods were used [413].…”
Section: Measuring the Nonenzymatic Antioxidant Capacity In Body Fmentioning
confidence: 99%
See 1 more Smart Citation